Biological Synthesis of Nanoparticles using bacteria - ahmadi, mandana (JOURNAL OF ADVANCES IN BIOLOGY, 2017)
Several ways such as physical, chemical and biological methods were used to synthesize metal nanoparticles. It has been confirmed that some microorganisms have the ability to produce nanoparticles. Numerous bacteria, fungi and plants have shown the potential to synthesise metallic nanoparticles. Bioreduction is one of the mechanisms to biosynthesize metal nanoparticles by microorganisms. Nanoparticles are formed on the surface of cell walls, and trapping of the metal ions on this surface is considered the first step in bioreduction. For example The bioreduction of metal ions and stabilization of the silver NPs occured due to an enzymatic process and It is suggested that nitrate reductase is one of the enzymes responsible in the bioreduction of ionic gold. The formation of nanoparticles with a particular size and morphology is ultimately determined by the interaction and biochemical processing activities of a specific microorganism and the influence of environmental factors such as pH and temperature